Exploring Self-Directed Informal Digital Learning for English Proficiency - Hikmatus Soimah; Zainuddin Zainuddin; Feri Ferdiyanto (Journal of English Language and Education, 2026)
The explosive growth of digital technology has had a substantial impact on English language learning by expanding access to learning resources beyond the classroom. Despite frequent exposure to English content via digital media, many learners continue to engage passively. The purpose of this study was to investigate the nature and activities of self-directed informal digital English learning (IDLE) and their impact on English proficiency. A qualitative descriptive method was used, with ten university students selected by purposive sampling. Data were gathered through interviews, observations, and documentation, then analysed using an interactive model. The data show that students participate in IDLE by watching YouTube videos, utilising apps like Duolingo, listening to podcasts, and communicating on social media platforms like TikTok and Instagram. Students presented both spontaneous and deliberate learning processes, with IDLE positively impacting vocabulary acquisition, listening comprehension, and speaking confidence. IDLE's efficacy is dependent on motivation, consistency, and self-regulated learning mechanisms.